The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/1531003511431737
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Pain Control Using a Thigh Pad Under the Elastic Stocking in Patients Following Venous Stripping: Results of a Case-Control Study

Abstract: The results of this case-control study show that the addition of a pad at thigh level under the elastic compression stocking significantly reduces pain experienced by patients during the week after stripping surgery by 49%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 3 publications
(4 reference statements)
1
10
0
9
Order By: Relevance
“…Benigni et al. 41 compared pain intensity on Days 1 and 7 and global mean pain during the week following stripping of the GSV in patients for whom either a pad had been added at thigh level under an MCS or patients with an MCS only. Pain was significantly reduced in the pad plus MCS group (p < 0.0001).…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benigni et al. 41 compared pain intensity on Days 1 and 7 and global mean pain during the week following stripping of the GSV in patients for whom either a pad had been added at thigh level under an MCS or patients with an MCS only. Pain was significantly reduced in the pad plus MCS group (p < 0.0001).…”
Section: Recommendationsmentioning
confidence: 99%
“…Three studies have shown that local high interface pressure, along the GSV at the thigh, can reduce pain. 40 42 …”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,35] In contrast to a comparison of limited daily values, the AUC method can provide an overall view of the evolution of individual patients' symptoms over a given period. A similar approach is used in the research of pain, [36] where sequential measurement is subject to similar fluctuations. Our results show that, in terms of the reduction in the HFS, the evolution of the HFS over the period of the study was significantly better in the BRN-01 group than in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…It is a standard treatment for a range of indications from prevention to postoperative care (6,12,13). By contrast, "eccentric" compression involves the additional use of pressure devices when attempting a specific increase in local pressure, such as along the course of an extracted or sclerosed vein (1,8,9).…”
Section: Schlüsselwörter Kompressionmentioning
confidence: 99%